Public Relation Strategy Analysis in Maintaining Image of PT Pos Indonesia (Persero) - Putra, Johni Eka; Sufa, Siska Armawati; Perbawasari, Susie; Brumadyadisty, Garry; Shany, Wildan Krisnarwanto Waranu (Journal of Business Management and Economic Development, 2024)
This scientific article delves deeply into the analysis of Public Relations (PR) strategies employed by PT Pos Indonesia (Persero), with a critical focus on strengthening corporate image. In the dynamic business landscape, a positive image is crucial for organizational success. The research adopts a comprehensive approach with descriptive qualitative analysis to evaluate the effectiveness of PT Pos Indonesia (Persero) PR initiatives. The study highlights the alignment of PR strategies with organizational goals, assessing their impact on shaping public opinion, and strengthening relationships with stakeholders. Exploration of the integration of traditional and digital communication channels is conducted to assess PT Pos Indonesia (Persero) adaptability in the evolving media landscape. Furthermore, the research tests crisis communication protocols to evaluate the organization's readiness in facing reputational risks. Drawing on theoretical frameworks and industry best practices, this article aims to provide insights into the strategic nuances of maintaining a positive corporate image. It offers practical recommendations for PT Pos Indonesia (Persero) and similar organizations. This research not only contributes to the scholarly understanding of PR strategies in the corporate realm but also serves as a valuable resource for practitioners and decision-makers striving to refine their communication tactics for sustained positive public perception.